Cultural Activities, Legal and Public Policy of Bali On Desa Pakraman and the Response of Prajuru the Traditional Village Management Kuta - Wesna Astara, I Wayan (Jurnal Ilmiah Peuradeun, 2018)
In the New era, Bali was hegemonized by the politics of the State's law against traditional villages. There is a response from Bali Provincial Government to create a policy to protect traditional villages in Bali. The power of Bali in the traditional village is maintaining Balinese culture based on Hinduism and the philosophy of Tri Hita Karana. Relevant critical theories in this article's discussion are public policy theory which is micro, hegemonic theory, power relation theory and deconstruction theory. Qualitative method with case study design in traditional village of Kuta is used as the research of cultural studies. The result of the research explains that public policy in Bali in defending traditional village is that Bali Provincial Government responds to state law politics by establishing Bali Provincial Regulation. However, when the Provincial Regulation of Bali No. 3 of 2001 on traditional village, the traditional village of Kuta responded to Article 3 paragraph (6) was not accepted by the prajuru and also received a response from the traditional village council, so the pros and cons of the traditional village in Bali emerged.